Scaffolding the Learning-to-Teach Process: A Study in an EFL Teacher Education Programme in Argentina - Maria Gimena San Martin (Universidad Nacional de Colombia, 2018)
This study seeks to examine how a supervisor scaffolds the student-teachers' learning-to-teach process in the context of one-to-one tutoring sessions in an English as a foreign language teacher education programme in Argentina. The findings indicate that scaffolding implies two main phases: a diagnostic and an intervention phase. Moreover, the supervisor was found to provide contingent help, which suited the student-teachers' perceived needs and/or difficulties. In conclusion, scaffolded help should be understood in relation to the function it serves and how it accommodates the students' level of understanding.